2017
DOI: 10.21859/ijcp-020204
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Cardiac Rehabilitation Care Plan on Quality of Life of Patients Undergoing Coronary Artery Bypass Graft Surgery

Abstract: Introduction: Cardiovascular surgeries are among the conventional surgeries aimed at increasing the survival rate and improving the quality of life of patients. This study aimed to evaluate the effect of cardiac rehabilitation on quality of life of patients undergoing Coronary artery bypass graft (CABG) surgery. Methods: This was a semi-experimental study performed on 160 patients undergoing CABG surgery. The rehabilitation program was carried out for 13 weeks (three sessions per week) in 40 sessions, six week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…A study conducted to evaluate the effectiveness of Cardiac Rehabilitation Care Plan on Quality of Life of Patients Undergoing Coronary Artery Bypass Graft Surgery, showed increased quality of life after 13 sessions in male and female post cardiac rehabilitation phase II. 12 A similar study done by Alexander et al also portrayed the same results after 12 week sessions of cardiac rehabilitation phase II on both the genders. 13 A study conducted by Muller-Nor horn et al also showed significantly improved quality of life of male and female patients after cardiac rehabilitation following the open heart surgery.…”
Section: Discussionsupporting
confidence: 65%
“…A study conducted to evaluate the effectiveness of Cardiac Rehabilitation Care Plan on Quality of Life of Patients Undergoing Coronary Artery Bypass Graft Surgery, showed increased quality of life after 13 sessions in male and female post cardiac rehabilitation phase II. 12 A similar study done by Alexander et al also portrayed the same results after 12 week sessions of cardiac rehabilitation phase II on both the genders. 13 A study conducted by Muller-Nor horn et al also showed significantly improved quality of life of male and female patients after cardiac rehabilitation following the open heart surgery.…”
Section: Discussionsupporting
confidence: 65%
“…A combination of these factors may cause financial and economic problems for the patient, healthcare systems, and society. In the case of more postoperative complications, overweight and obese patients are more likely to develop underlying conditions such as diabetes [14].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the potentially harmful consequences, patients who are satisfied and able to accept changes in their body image experience improvements in their self-esteem, anxiety, and depression (Begovic-Juhant et al, 2012 ). These individuals are more likely to adapt their lifestyles and daily activities successfully (Lightfoot, 2010 ), which can help reduce or delay the progression of the disease, minimize costs, and enhance their overall quality of life (Ballan & Lee, 2007 ; Begovic-Juhant et al, 2012 ; Masoumi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%